Peran Humas Dalam Membangun Citra Pemerintahan Sumatera Utara Pada Kantor Biro Humas Gubernur - Dolly Indra Syahputra; Yan Hendra; Taufik Wal Hidayat (PERSPEKTIF, 2018)
Thisresearchismotivatedbytheimportance ofpublic relationsroleinbuildingthe imageofgovernment.Thepurposeofthisstudy istoexplaintheroleof publicrelationsin buildingtheimageofthegovernmentofNorthSumatra.Theoriesusedinthisstudyinclude the theoryofcommunication,public relationsandthe theory ofimage. The type ofthis research isqualitative research usingqualitativedecriptive method,Researchdatacollected byinterviewing someresource. Resourcepersonsofthisresearcharepersonnelinpublic relationsdepartmentof North  Sumatera  such  as  public  relations  sub-chairman  and  four  public  relations  staff, researchresultshowsthatpublicrelationsrole inbuildingimageofNorthSumateraisseen frompublic relationsrole asexpertadvisor,public relationsroleasproblem solver,public relationsrole ascommunicationfacilitator.Overallitcanbeexplainedthatthe public relationsof NorthSumatragovernmenthasdoneitsrolein building theimageofNorth Sumatera government.